Inhibition of Corneal Neovascularization by Topical and Subconjunctival Tigecycline - Sertan Goktas; Ender Erdogan; Rabia Sakarya; Yasar Sakarya; Mustafa Yılmaz; Muammer Ozcimen; Nejat Unlukal; Ismail Alpfidan; Fatih Tas; Erkan Erdogan; Abdulkadir Bukus; Ismail Senol Ivacık (Journal of Ophthalmology)
Objective. To investigate the effects of topical and subconjunctival tigecycline on the prevention of corneal neovascularization. Materials and Methods. Following chemical burn, thirty-two rats were treated daily with topical instillation of 1 mg/mL tigecycline (group 1) or subconjunctival instillation of 1 mg/mL tigecycline (group 3) for 7 days. Control rats received topical (group 2) or subconjunctival (group 4) 0.9% saline. Digital photographs of the cornea were taken on the eighth day after treatment and analyzed to determine the percentage area of the cornea covered by neovascularization. Corneal sections were analyzed histopathologically. Results. The median percentages of corneal neovascularization in groups 1 and 3 were 48% (95% confidence interval (CI), 44.2–55.8%) and 33.5% (95% CI, 26.6–39.2%), respectively. The median percentages of corneal neovascularization of groups 1 and 3 were significantly lower than that of the control group (P=0.03 and P<0.001, resp.). Histologic examination of samples from groups 1 and 3 showed lower vascularity than that of control groups. Conclusion. Topical and subconjunctival administration of tigecycline seems to be showing promising therapeutic effects on the prevention of corneal neovascularization. Furthermore, subconjunctival administration of tigecycline is more potent than topical administration in the inhibition of corneal neovascularization.